The Relationship Between Mother's Knowledge And Attitude About High Risk Pregnancy In Pulo Brayan Medan Health Center - BR. Sebayang, Wellina (SEAN Institute, 2023)
Some complications that may occur in high-risk pregnancies, especially women who are pregnant at the age of more than 35 years, include the fetus in the womb experiencing genetic problems and congenital abnormalities. According to a number of theories, women at a greater age are at greater risk of having a baby born with genetic disorders. The purpose of this study was to analyze the relationship between knowledge and attitudes with a high risk of pregnancy at the age of more than 35 years in the working area of ​​the Pulo Brayan Health Center, Medan. This type of research is an analytic survey using a cross-sectional approach by means of observation and data collection at one time. The statistical test used was the chi square test with a significance degree of p value 0.05 The results showed that 80% of mothers with less knowledge and 85% of negative attitudes experienced high-risk pregnancies, namely pregnant at age > 35 years. There is a significant relationship between knowledge and the risk of pregnancy over 35 years, p value 0.001 and there is an attitude relationship with the risk of pregnancy over 35 years, p value 0.000. Suggestions for the Puskesmas to optimize health education and proper handling of high-risk pregnancies